Enhancing electrochemical performance of alginate–PVA solid blend electrolytes via H+ ion doping for supercapacitor applications - N. M., Ghazali; N. F., Mazuki; Mohd Herwan, Sulaiman; Aoki, K.; Nagao, Y.; Ahmad Salihin, Samsudin (Elsevier Ltd, 2024)
This study investigates the enhancement of electrochemical performance in alginate–polyvinyl alcohol (PVA) solid blend electrolytes through H+ ion doping for supercapacitor applications. Employing the solution casting method, we tailored electrolyte systems doped with nitric acid (HNO3). Impedance studies reveal a substantial increase in ionic conductivity (2.71 × 10−4 S cm−1 at room temperature) with 3 M HNO3 doping. Fourier-transform infrared spectroscopy and transference number measurements confirm the effective protonation of the polymer matrix. Temperature-dependent behavior analysis demonstrates robust performance across various thermal conditions. Linear sweep voltammetry studies showcase excellent electrochemical stability, while galvanostatic charge-discharge profiles exhibit reliable cyclic performance, with an average specific capacitance of approximately 6.76 F/g. This research underscores the potential of tailored solid blend electrolytes doped with H+ ions to elevate supercapacitor technology.